A tutorial on the Loewner-based system identification and structural health monitoring approach for mechanical systems. - Dessena, Gabriele (Cranfield University, 2023)
The tutorial should be considered complementary material for the article "A Loewner-based system identification and structural health monitoring approach for mechanical systems" (DOI: 10.1155/2023/1891062). The tutorial illustrates, via a simple example, the capability of the Loewner Framework for System Identification and Structural Health Monitoring. The second goal of this tutorial is to make available a Loewner Framework program for MATLAB to the public based on the published work. Please cite [1-5] when using this software for your work or research, Thank you. This tutorial is linked to the following article: G. Dessena, M. Civera, L. Zanotti Fragonara, D. I. Ignatyev, J. F. Whidborne, A Loewner-based system identification and structural health monitoring approach for mechanical systems, Structural Control and Health Monitoring, Vol. 2023 (2023). (DOI: 10.1155/2023/1891062) The repository entry contains five files: 1. data_9dof.mat: the data for the tutorial model; 2. LF_id.m: the script for the LF-based System Identification; 3. loewner.m: the Loewner Matrix function; 4. LF_tutorial.mlx: the LF tutorial in MATLAB live mode 5. LF_tutorial.pdf: the LF tutorial in pdf. The program was created in MATLAB 2020a, compatibility with earlier or later versions is not guaranteed. References [1] G. Dessena, M. Civera, L. Zanotti Fragonara, D. I. Ignatyev, J. F. Whidborne, A Loewner-based system identification and structural health monitoring approach for mechanical systems, Structural Control and Health Monitoring, Vol. 2023 (2023). (DOI: 10.1155/2023/1891062) [2] G. Dessena, A Loewner-based system identification and structural health monitoring approach for mechanical systems, CORD repository (2021) (DOI: 10.17862/cranfield.rd.16636279) [3] A. J. Mayo, A. C. Antoulas, A framework for the solution of the generalized realization problem, Linear Algebra and its Applications 425, pp. 634–662 (2007). (DOI:10.1016/j.laa.2007.03.008) [4] S. Lefteriu, A. C. Antoulas, A New Approach to Modeling Multiport Systems From Frequency-Domain Data, IEEE Transactions on Computer-Aided Design of Integrated Circuits and Systems, Vol. 29, No. 1, pp. 14–27 (2010). (DOI: 10.1109/TCAD.2009.2034500) [5] S. Lefteriu, A. C. Ionita, A. C. Antoulas, Modeling Systems Based on Noisy Frequency and Time Domain Measurements, Lecture Notes in Control and Information Sciences, vol. 398/2010, 365-368 (2010). (DOI: 10.1007/978-3-540-93918-4_33)
Keywords: Loewner Matrix; Loewner Framework; Realization Problem; System Identification; Structural Health Monitoring; Frequency Response Functions; Modal Analysis; Simulation and Modelling